ANALYSIS OF PHYSICAL MECHANICAL PROPERTIES OF PURPLE KNIT FABRICS KNITTED FROM SPUN COTTON NITRO YARN (Conferencea, 2023)
This article is effective from local raw materials for use, feathered from spun cotton-nitron yarn Research works were carried out on the physical and mechanical properties of knitted fabric.